Bioclimatic vs conventional building: experimental quantification of the thermal improvements. (September 2017) - Soutullo, S.; Sánchez, M.N.; Enríquez, R.; Olmedo, R.; Jimenez, M.J.
Abstract: This paper focuses on the thermal comparison between two full-size occupied buildings located in Madrid, built considering different constructive criteria. Hourly temperature distributions have been calculated during the working timetable to assess indoor dynamic processes. In both cases there are less than 4% of outliers, reaching lower standard deviations in the bioclimatic offices. Temperature oscillations have shown different thermal profiles depending on the user's behavior. High percentages of neutral sensation and low values of people dissatisfied have been obtained. The bioclimatic building has obtained higher comfort measures as a function of the thermal balances and the global primary energy consumption.